(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The yield of seed size tubers was assessed in five standard potato cultivars (Cardinal, Multa, Ailsa, Heera, and Dheera) in relation to dates of dehaulming (65, 70, and 80 days after planting) in a Seed Potato Production Farm, Debijong, Panchagarh during 1996-97 and 1997-98. Dehaulming at 70 days gave maximum seed size tubers (19.75 t/ha ≈ 76%) but significantly identical to 75 days (19.56 t/ha ≈70%) and 80 days (18.69 t/ha ≈ 63%). Considering all the parameters studied, the performance of Heera proved to be best among the cultivars grown. Among the cultivars, the maximum seed tuber yield was recorded from Cardinal at 80 DAP followed by Heera and Cardinal at 70 DAP, Dheera and Ailsa at 75 DAP. In general, most of the cultivars gave the maximum seed tuber yield when the crop was dehaulmed at 70 and 80 DAP and the lowest from 65 DAP. Key Words: Dehaulming, potato, seed production. DOI: 10.3329/bjar.v34i3.3970 Bangladesh J. Agril. Res. 34(3) : 443-448, September 2009